Water-induced finger wrinkles do not affect touch acuity or dexterity in handling wet objects. - Julia Haseleu (Public Library of Science (PLoS), 2014)
Human non-hairy (glabrous) skin of the fingers, palms and soles wrinkles after prolonged exposure to water. Wrinkling is a sympathetic nervous system-dependent process but little is known about the physiology and potential functions of water-induced skin wrinkling. Here we investigated the idea that wrinkling might improve handling of wet objects by measuring the performance of a large cohort of human subjects (n = 40) in a manual dexterity task. We also tested the idea that skin wrinkling has an impact on tactile acuity or vibrotactile sensation using two independent sensory tasks. We found that skin wrinkling did not improve dexterity in handling wet objects nor did it affect any aspect of touch sensitivity measured. Thus water-induced wrinkling appears to have no significant impact on tactile driven performance or dexterity in handling wet or dry objects.